Design and Construction of A Pico Hydro Power Plant for Electrification in Singogalih Village - Wildan Surya Wijaya; Alif Dwi Prasetyo; Akhmad Solikin; muhammad imam malik (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Energy is a vital necessity in supporting societal activities; however, dependence on non-renewable fossil fuels poses sustainability challenges. Therefore, the development of New and Renewable Energy (NRE) serves as a strategic solution, especially in rural areas that still face limited access to electricity. This study examines the implementation of a Pico Hydro Power Plant (PLTPH) based on an Archimedes Screw turbine in Singogalih Village, Tarik Sub-district, Sidoarjo Regency, as an environmentally friendly alternative for providing electricity for lighting in rice field areas. The system utilizes water flow from irrigation channels to drive the turbine and generate electricity, which is then regulated through a Control Charger (CC) to power LED lamps. Testing was conducted over three weeks by observing generator rotation (RPM), voltage, and electric current at three different times each day. Measurement results showed an increase in system performance from week to week. RPM rose from 226.9 to 384.4, voltage increased from 6.5 V to 11.0 V, and current rose from 0.49 A to 0.82 A. This improvement indicates that the PLTPH system is capable of operating consistently and efficiently in converting water’s kinetic energy into electrical energy under existing flow conditions, reflecting the enhanced performance of the generator and the system as a whole during the testing period. The findings demonstrate that a PLTPH using an Archimedes Screw turbine can serve as a sustainable, self-reliant, and appropriate lighting solution for rural areas with continuous water flow potential.